Kosovo : Country Environmental Analysis - World Bank (Washington, DC, 2013)
A Kosovo CEA is a World Bank analytical tool used to integrate environmental issues into development assistance strategies, programs, and projects. To that end, the CEA synthesizes environmental issues, highlights the environmental and economic implications of development policies, and evaluates the country's environmental management capacity. Kosovo is landlocked and possesses many mineral resources, mainly coal, lead, zinc, chromium, and silver. Current industrial activity and a legacy of former practices have heavy health and environmental impacts and generate economic losses. The environmental priorities for the next five years are completing environmental legislation in harmony with the European Union (EU) acquits; gradually fulfilling EU standards and efficiently carrying out and incorporating environmental legislation and methodologies in all sectors; and setting up and expanding institutions for the implementation of environmental policies. Kosovo seems to spend less on environmental protection as a share of Gross Domestic Product (GDP) than some neighboring EU-10 countries. Waste management, water, and air quality have been the main priorities for capital expenditures in recent years and much of the capital spending on environmental projects has been made by municipalities, as they have a core competency to provide several environmental services, including green areas and waste management. A hefty share of environmental financing also seems to come from international donors.